2017
DOI: 10.3389/fphar.2017.00473
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Alleviates Endothelial-to-Mesenchymal Transition in Glomeruli via Suppression of Oxidative Stress and TGF-β1 Signaling

Abstract: Statins may decrease chronic kidney diseases (CKDs) risk, but their underlying molecular mechanisms are not completely understood. Recent studies indicate Endothelial-to-mesenchymal transition (EndMT) plays an important role contributing to renal interstitial fibrosis. In the present study, we first investigated whether lovastatin could ameliorate renal fibrosis via suppression of EndMT and its possible mechanism. In vitro experiments, lovastatin significantly ameliorated microalbuminuria and pathologic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Accumulating evidence has shown that glomerular structural changes are diagnostic indicators for early DN. 25 In 2017, an investigation by Ma 26 These findings suggest that the levels of collagen and fibronectin are also increased in DN. Indeed, Masson's trichrome staining showed collagen accumulation in early-stage DN (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that glomerular structural changes are diagnostic indicators for early DN. 25 In 2017, an investigation by Ma 26 These findings suggest that the levels of collagen and fibronectin are also increased in DN. Indeed, Masson's trichrome staining showed collagen accumulation in early-stage DN (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that glomerular structural changes are diagnostic indicators for early DN . In 2017, an investigation by Ma et al indicated that levels of TGF‐β1 and p‐Smad2/3 were increased in DN . These findings suggest that the levels of collagen and fibronectin are also increased in DN.…”
Section: Discussionmentioning
confidence: 99%
“…50 The clinically-approved cholesterol lowering agents, the "statins" family, diminish EMT, TGF-β signaling and oxidative stress in glomerular cells. 75,[154][155][156] Others (Figure 14). Therapeutic attempts have also included targeting histone H4 acetylation, NDI-010976/ND630 (123) RO6842262 (124) GLPG1690 (125) BMS-986020/AM152 (126) roflumilast (127) pentoxifylline (128) sildenafil (129) PF-00489791 (130) inhibition of the Ca 2+ -activated K + channel (KCa3.1), the mineralocorticoid/aldosterone receptors or the vitamin D-dependent pathways.…”
Section: Inhibitors Of Metabolic Pathways (mentioning
confidence: 99%
“…Erlotinib(74), the second approved EGFR inhibitor, reversibly binds to the ATP site of the receptor. Afatinib(75), is an irreversible covalent inhibitor of EGFR and ErbB-2/HER2. Lapatinib(76), is an orally active dual HER2/EGFR inhibitor of the ATPbinding pocket of the kinase domains.…”
mentioning
confidence: 99%
“…The number of animal microvessels per group and eight fields of view per tissue were counted. All measurements were performed in a blinded manner [24].…”
Section: Pathologic Assessment Of Angiogenesismentioning
confidence: 99%